Analisis Pengaruh Besar Sudut Potong & Ketebalan Mata Pisau Pada Mesin Pencacah Daun Kering Terhadap Hasil Cacahan - Izhar Amri, Muhammad; Bahri Widodo, Syamsul; Arif, Zainal (JURUTERA - Jurnal Umum Teknik Terapan, 2025)
Technology development aims to simplify work and improve equipment efficiency, including modifying the dry leaf chopper to optimize chopping results. This modification focuses on variations in the angle and thickness of the blade to obtain finer shreds that meet the needs. This study aims to determine the most effective cutting angle and blade thickness in producing the best shreds. The research was conducted at the Mechanical Engineering Laboratory of Samudra University in August 2024. The blades used varied in cutting angles of 30°, 20°, and 10° and thicknesses of 3 mm and 5 mm. The quantitative analysis method was applied in this study using the independent sample T-test to evaluate the effectiveness of each variable. The results showed that a blade angle of 10° was the most effective angle for softening the chopped dry leaves. In addition, the most optimal blade thickness to produce fine shreds was 3 mm. This modification shows a significant improvement compared to the previous shredder, which used an angle and blade thickness with less than optimal results. With this research, it is expected that the dry leaf shredder can function more efficiently and produce shreds that meet the standards